Mrs. Myrlie Evers, 'For us the living' (1973)
[00:00:01] Explanation of the "Convocation Series" and the purpose for the series by Dr. Dale Andrews. [00:07:20] Introduction by student Fred Johnson. [00:09:08] Fred Johnson introduces Myrlie Evers. [00:14:45] Myrlie Evers begins her speech by thanking Fred Johnson and being at Cal Poly. [00:16:55] Explains the use of the title ‘For us the living' with remarks towards her late husband Medgar Evers. [00:19:45] Reflection on the death of her husband. [00:21:08] Internal difficulties of leaving the state of Mississippi and the realization of a national problem. [00:22:29] The cancers of our society and refusing to admit there is a problem. [00:25:22] Progress and where the nation is going. [00:29:00] The constant reminder that things have not really changed. [00:30:20] The mood of moving from the 60s to the 70s and the lack of apathy. [00:34:37] Disappointment with the youth vote. [00:35:20] The discouraged feeling of leadership and the struggle of the movements. [00:39:20] "We sit back, and we do nothing until it becomes too hot". [00:41:30] "What can we do?". [00:47:00] Being asked to run for congress. [00:50:50] Getting the young people interested. [00:52:00] Final remarks regarding ‘For us the living' and making America a better place to live. [00:56:12] Myrlie Evers speech ends. [00:56:40] Questions and Answers with Myrlie Evers. [00:57:22] What are the most significant changes that have occurred in the evolution of the black man in Southern politics? [01:03:15] What do I think is the primary role of the Black woman in terms of furthering the cause of Blacks? [01:11:45] Do you think mass action is the most effective means of change in our society? [01:15:19] Do you feel that all minority groups should band together and fight for their right on a common ground? [01:18:37] Would you agree at least in part that Vietnam is an extension of America's racism? [01:21:00] Can you see the time in the near future that we may respect and enjoy each other without the great barriers of race and religion that seem to be distrust and insensitivity to often today? [01:24:30] Is there a young emerging leader among the Black culture who hopes to continue where Martin Luther King left off? [01:28:52] Now that the intense racial strife of the sixties is over, do you feel that less emphasis should be applied to desegregation and more on solving urban decay and the improvement of the human environment? [01:32:57] Questions from the audience. [01:38:44] Recording ends.